SISTEM JUAL BELI ONLINE PERSPEKTIF HUKUM EKONOMI SYARIAH (Studi Pada Forum Facebook Jual Beli Tanjab Timur Jambi) - Misnawati; Nilfatri; Zeni Sunarti (Lembaga Pengembangan Kinerja Dosen, 2022)
This research contains a research on the system in the review of Islamic Economic Law in the process of buying and selling online on the Facebook group Buying and Selling Tanjab Timur Jambi. This research uses descriptive qualitative research method. The results of this study found that there are several opinions that say that buying and selling must meet the requirements of them in the same place. however, in online buying and selling transactions at the Tanjab Timur Jambi Buying and Selling Facebook Forum, sellers and buyers meet in one assembly, namely the so-called virtual assembly. Sellers and buyers are not in one particular place in a physical sense and transactions may be made from different countries.